2015
DOI: 10.3389/fpsyg.2015.01510
|View full text |Cite
|
Sign up to set email alerts
|

Improving reading skills in students with dyslexia: the efficacy of a sublexical training with rhythmic background

Abstract: The core deficit underlying developmental dyslexia (DD) has been identified in difficulties in dynamic and rapidly changing auditory information processing, which contribute to the development of impaired phonological representations for words. It has been argued that enhancing basic musical rhythm perception skills in children with DD may have a positive effect on reading abilities because music and language share common mechanisms and thus transfer effects from the former to the latter are expected to occur.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 61 publications
(68 reference statements)
6
55
1
Order By: Relevance
“…Finally, the protocol of an ongoing study testing the effect of a multiple-session tDCS intervention combined with a cognitive training for DD has been recently reported (Cancer and Antonietti, 2017 ). A sample of undergraduate students with a diagnosis of DD has been involved in an intervention comprising a novel rhythm-based reading training (Bonacina et al, 2015 ; Cancer et al, 2016 ) paired with tDCS for 10 daily sessions over 2 weeks. The left temporo-parietal region was stimulated at a constant current of 1.5 mA for 20 min, and the electrode montage replicated the one used by Costanzo et al ( 2016a ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the protocol of an ongoing study testing the effect of a multiple-session tDCS intervention combined with a cognitive training for DD has been recently reported (Cancer and Antonietti, 2017 ). A sample of undergraduate students with a diagnosis of DD has been involved in an intervention comprising a novel rhythm-based reading training (Bonacina et al, 2015 ; Cancer et al, 2016 ) paired with tDCS for 10 daily sessions over 2 weeks. The left temporo-parietal region was stimulated at a constant current of 1.5 mA for 20 min, and the electrode montage replicated the one used by Costanzo et al ( 2016a ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the RCT results of Flaugnacco et al ( 2015 ) [17] showed better performance of the music group on reading skills in comparison to the control group. Using an experimental design, Bonacina et al ( 2015 ) [20] randomly assigned 11–14 year-old children to a computer-assisted, rhythmic reading training (RRT) ( n = 14) or a control group ( n = 14), for which no specific activity addressed to improve reading skills was carried out. Results indicated that RRT had a positive effect on both reading speed and accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, another strand of literature has uncovered associations between musical skills-especially aspects related to rhythm-and phonological www.nature.com/scientificreports/ awareness in TD individuals 36,38,[48][49][50] . Individuals with DD have also been reported to benefit from training in sensorimotor synchronization to a pulse delivered by a metronome 51 , and more generally from music training 52 . Previous studies focusing on sensorimotor synchronization showed that the sensorimotor coupling is generally well-preserved in the dyslexic population (though sometimes dyslexics are less precise than controls in tapping), but that neural rhythmic entrainment is atypical in individuals with dyslexia 41,[65][66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing evidence that rhythmic abilities are associated to phonological awareness, an essential precursor of reading 36,38,[48][49][50] . The link between rhythm and phonological awareness emerges also in studies showing that music and rhythmic training improves phonological awareness and reading skills 48,[51][52][53][54][55] . Rhythm facilitates segmentation of the continuous speech into units of different sizes, phrases, words, phonemes and contributes to the recovery of phonological words, as shown in several studies on infants [56][57][58][59][60][61] .…”
mentioning
confidence: 94%